Sufism and Pluralism in the Indian Subcontinent: A Spiritual Response to Diversity - Ganai, Nasir Ahmad (Islam Transformatif : Journal of Islamic Studies, 2025)
Abstract This study examines how Sufi thought and practice contributed to the emergence of a pluralistic social order in medieval India. The Indian subcontinent has long been recognized for its rich cultural variety and religious differences. Sufism in the Indian subcontinent evolved as a powerful moral and spiritual movement that transcended sectarian and cultural boundaries. The primary objective of the research is to explore the ways in which Sufi teachings on love, service, and universal brotherhood functioned as a spiritual response to religious and cultural diversity. Methodologically, the study adopts a historical-analytical approach, drawing upon the writings of early Chishti Sufis, archival records, and the interpretations of modern scholars such as Khaliq Ahmad Nizami. Through a close reading of Sufi texts and a contextual analysis of their socio-religious milieu, the paper identifies how the khanqah system fostered social inclusivity and intercommunal harmony. The findings reveal that Sufi spirituality provided an ethical and emotional framework that enabled diverse communities to coexist without erasing their distinct identities. Ultimately, the paper argues that Sufism’s pluralistic ethos remains a vital model for addressing contemporary challenges of intolerance and fragmentation in multicultural societies. Abstrak Studi ini meneliti bagaimana pemikiran dan praktik Sufi berkontribusi pada munculnya tatanan sosial pluralistik di India abad pertengahan. Subkontinen India telah lama dikenal karena kekayaan keragaman budaya dan perbedaan agamanya. Sufisme di subkontinen India berkembang sebagai gerakan moral dan spiritual yang kuat yang melampaui batas-batas sektarian dan budaya. Tujuan utama penelitian ini adalah untuk mengeksplorasi cara-cara di mana ajaran Sufi tentang cinta, pengabdian, dan persaudaraan universal berfungsi sebagai respons spiritual terhadap keragaman agama dan budaya. Secara metodologis, studi ini mengadopsi pendekatan historis-analitis, dengan mengacu pada tulisan-tulisan Sufi Chishti awal, catatan arsip, dan interpretasi para sarjana modern seperti Khaliq Ahmad Nizami. Melalui pembacaan cermat teks-teks Sufi dan analisis kontekstual lingkungan sosial-agama mereka, artikel ini mengidentifikasi bagaimana sistem khanqah mendorong inklusivitas sosial dan harmoni antar komunitas. Temuan menunjukkan bahwa spiritualitas Sufi menyediakan kerangka kerja etis dan emosional yang memungkinkan berbagai komunitas untuk hidup berdampingan tanpa menghapus identitas mereka yang berbeda. Pada akhirnya, artikel ini menunjukkan bahwa etos pluralistik Sufisme tetap menjadi model penting untuk mengatasi tantangan kontemporer berupa intoleransi dan fragmentasi dalam masyarakat multikultural.